2016
DOI: 10.1093/jrr/rrw017
|View full text |Cite
|
Sign up to set email alerts
|

A report that Fukushima residents are concerned about radiation from Land, Food and Radon

Abstract: The Great East Japan Earthquake and subsequent TEPCO Fukushima Daiichi nuclear disaster occurred on 11 March 2011, which caused the leakage of radioactive materials into the environment. In this study, we report public concerns about radiation in Fukushima and Tokyo almost one year after the nuclear disaster. We examined the public concerns by analyzing the data from 1022 participants, 555 in Fukushima and 467 in Tokyo. They were asked whether they were concerned about radiation from some of six different type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“… Taking in radioactive materials in water or food, such as in wild foods in contaminated areas ( internal exposure ). Some people are worried about the contamination of the water supply systems and food chain [ 73 , 74 , 75 , 76 ]. …”
Section: Resultsmentioning
confidence: 99%
“… Taking in radioactive materials in water or food, such as in wild foods in contaminated areas ( internal exposure ). Some people are worried about the contamination of the water supply systems and food chain [ 73 , 74 , 75 , 76 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Karasawa & Todayama, 2013). As many researchers have emphasised the importance of risk communication between the public and government agencies (Shineha & Tanaka, 2018;Tamari et al, 2016), the agencies may need to be orientated more toward interactive dialogue rather than "educating" the public.…”
Section: Discussionmentioning
confidence: 99%
“…DA has also been reportedly related to the risk perception of radiation (RPR). Numerous researchers have observed that fear of radiation is widespread among Fukushima prefecture residents (e.g., McCurry, 2011;Suzuki et al, 2015); hence, the importance of solid information about the determinants of RPR has been noted by various scholars (e.g., Goodwin, Takahashi, Sun, & Gaines, 2012;Tamari et al, 2016).…”
Section: Da and Risk Perception Of Radiationmentioning
confidence: 99%